Nonlinear Relationship Between Coronary Perfusion Pressure and In-Hospital Outcomes After Infant Congenital Heart Surgery - Tongkai Ge; Dandong Luo; Qiuji Wang; Jimei Chen; Huanlei Huang; Chongjian Zhang (Children)
Objectives: Our goal was to evaluate the associations between postoperative coronary perfusion pressure (CPP) values and in-hospital outcomes in infants after congenital cardiac surgery. Our goal was to assess the relationship between postoperative coronary perfusion pressure (CPP) values and in-hospital outcomes in infants following congenital cardiac surgery. Methods: In this study, we conducted a retrospective analysis on a cohort of 296 consecutive infant patients (aged 31–120 days) who underwent congenital cardiac surgery between 1 January 2019 and 30 April 2019. A total of 208 patients undergoing congenital cardiac surgery were included. The primary poor in-hospital outcome was prolonged recovery. The association between CPP level and in-hospital outcomes was determined using logistic regression analysis. We also used restricted cubic splines (RCSs) to evaluate the nonlinear relationship. Results: Our study included 208 participants, among whom the mortality rate was 1%. Prolonged hospital length of stay (LOS) was defined as more than 15 days, prolonged mechanical ventilation (MV) stay as more than 96 h, and prolonged intensive care unit (ICU) LOS as more than 403 h. In univariate analyses, we found that prolonged recovery was associated with both low CPP levels (p < 0.001, OR 4.28, 95% CI 1.94–9.46) and high CPP levels (p = 0.003, OR 3.39, 95% CI 1.52–7.58). In multivariable logistic regression analysis, after full adjustment, low CPP levels and high CPP levels were significantly associated with prolonged recovery (p = 0.005, OR = 3.72, 95% CI 1.48–9.35 and p < 0.001, OR = 6.04, 95% CI 2.32–15.72, respectively). We observed that the relationship between CPP level and poor in-hospital outcomes was U-shaped in a two-piecewise linear regression analysis. We found that the inflection point of CPP level for prolonged recovery was 47 mm Hg. Conclusion: The CPP levels exhibited a nonlinear relationship with poor in-hospital outcomes.